The exploitation of western and southern deserts in Iraq for the production of solar energy - Ahmed Zkear Abass; D. A. Pavlyuchenko (International Journal of Electrical and Computer Engineering (IJECE), 2019)
We have, an overview is presented of the potential future demands and possible supply of solar energy to Iraq. Solar energy, which is clean, unlimited, and environmentally friendly, is presented as a renewable energy resource. Many problems such as CO2 emissions, industry, human activities, and electricity distribution grids have attracted much attention because of the current state of crude oil production and its prices. Moreover, estimations of solar radiation levels and of the efficiencies of photovoltaics (PVs), concentrated solar power (CSP), and solar chimney towers, have all been investigated. Those systems that combine various sources of energy are called hybrids and they have received much attention in recent decades. The basic features of solar radiation in Iraq are outlined, and the selection of those sites with potential for development of solar plants is based on the local largest solar radiation. Moreover, longitudinal and latitudinal orientation, wind, solar intensity, dust, temperature, rain, humidity, and pollution factors are all considered in the calculation of PV/CSP efficiencies. We know there is an abundance of fossil fuels in Iraq, energy shortages began in 1991 because of the perturbation caused by the full ruin of the country. The obvious renewable energy resource available in Iraq is the solar energy, and its exploitation would provide a means to reduce CO2 emissions from the burning of fossil fuels and to achieve self-sufficiency of electric energy and export the rest to neighboring countries. Solar energy is becoming increasingly important because of the climatic change in the form of global warming.